ANALISIS PENGARUH KEPEMILIKAN INSTITUSI, RASIO TOBIN Q, AKRUAL PILIHAN, TARIF EFEKTIF PAJAK, DAN BIAYA PAJAK DITUNDA TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN PUBLIK - Hotman T Pohan (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2009)
The effort of tax planning by management or owner of corporate to decreas pay off tax obligation of corporation.Tax avoidance is part of tax planning wihtout conflict with tax rule,meanwhile tax evasion is tax planning that to conflict with tax rule .There are two kind of income for tax,first is income before tax which its calculation base on generally accepted accounting principles,second is income tax which calculation base on rule of statutory,however income tax can not be known directly therefore was is need estimated number for its proxy. The different kind of income is namely book-tax differrent(BTD),its proxy for tax avoidance. The objective of this research is to prove the factors that assumed influence book -tax different significantly or not. The methodology of this research is multivariate analysis with independent variables which are institutional ownership, Tobin Q, income smoothing, discreanary accrual proxy for earning management, efective tax rate, and deferred tax expense.The result of this research, is to prove that earning management influence negatively and significantly toward book-tax difference, income smoothing influence positively and significantly, efective tax rate influence positive and significantly toward boo-tax difference ,meanwhile institutional ownership and deferred tax expense has no influence toward book-tax difference,simultaniosly all factors significantly influence toward book-tax different with coefficient determination 26,5%.